Matching-adjusted indirect comparison: secukinumab versus infliximab in biologic-naive patients with psoriatic arthritis. (26th February 2019) - Strand, Vibeke; McInnes, Iain; Mease, Philip; Nash, Peter; Thom, Howard; Kalyvas, Chrysostomos; Hunger, Matthias; Gandhi, Kunal; Pricop, Luminita; Jugl, Steffen; Choy, Ernest
Aim: To compare secukinumab with infliximab in biologic-naive patients with psoriatic arthritis using matching-adjusted indirect comparison.Patients & methods: Individual patient baseline data for secukinumab were matched to published aggregate data for infliximab by key baseline characteristics, with matching weights determined by logistic regression, and used to recalculate American College of Rheumatology (ACR) responses for secukinumab, for comparison with infliximab.Results: There were no differences in outcomes between secukinumab and infliximab at weeks 6/8 and 14/16. At weeks 24 and 54/52, ACR 20 responses were higher with secukinumab 150 mg than infliximab. At week 54/52, ACR 20/50 responses were higher for secukinumab 300 mg than infliximab.Conclusion: In the mid to long term, patients receiving secukinumab were more likely to achieve ACR 20/50 responses than those receiving infliximab.